REGULAR AND IRREGULAR CLIMATIC CYCLES AND THE BELEMNITE MARLS (PLIENSBACHIAN, LOWER JURASSIC, WESSEX BASIN) - Weedon, G; Jenkyns, H (1990)
Time series of carbonate and organic-carbon values are reported for 10.5 m of the Belemnite Marls. The light and dark marl beds form decimetre-scale couplets and metre-scale bundles. Light marls are carbon-poor and carbonate-rich whereas dark marls and laminated shales are carbon-rich and carbonate-poor. Sediment composition appears to have been indirectly controlled by climate; the regular couplets may record orbital-precession cycles (20 ka). However, the bundles cannot be linked to changes in eccentricity; rather they apparently record irregular, large-amplitude climatic variations with periods of a few hundred thousand years. It should not be assumed that 100-400 ka cyclicity in climate-related sedimentary sequences can be explained only by orbital forcing.